2017
DOI: 10.1016/j.jid.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Protects Human Melanocytes from H2O2-Induced Oxidative Stress by Activating Nrf2

Abstract: The prevention of hydrogen peroxide (HO)-induced oxidative stress has proved to be beneficial to vitiligo patients. Simvastatin possesses antioxidative capacity and has shown protective effect in various oxidative stress-related diseases. However, whether simvastatin can protect human melanocytes against oxidative stress has not been investigated. In this study, we initially found that pretreatment with 0.1 μmol/L to 1.0 μmol/L simvastatin led to increased cell viability and decreased cell apoptosis of melanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 40 publications
3
46
0
1
Order By: Relevance
“…Extremely high levels of H 2 O 2 have been observed in vitiligo epidermis, and these are responsible for melanocyte loss . ROS accumulation directly induces melanocyte damage and causes an autoimmune response that subsequently results in melanocyte destruction …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extremely high levels of H 2 O 2 have been observed in vitiligo epidermis, and these are responsible for melanocyte loss . ROS accumulation directly induces melanocyte damage and causes an autoimmune response that subsequently results in melanocyte destruction …”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms are not fully understood, although oxidative stress is one possible pathogenic event . The accumulation of reactive oxygen species (ROS), mainly consisting of H 2 O 2 , superoxide anions and hydroxyl radicals, in melanocytes induces apoptosis and might therefore be involved in melanocyte destruction . Consequently, the application of antioxidants to ameliorate oxidative damage might represent a potential therapeutic approach for the treatment of vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of atorvastatin and simvastatin on oxidative stress markers in rats with hyperhomocysteinemia (Hhcy) were analyzed, and simvastatin was shown to have a superior antioxidant activity compared with that of the atorvastatin, independent of its effects on the lipid profile, but dependent on the homocysteine concentration. Simvastatin was shown to protect human melanocytes from H 2 O 2 -induced oxidative stress by activating NRF2, which indicates that this compound may be used for vitiligo treatment [83]. Sufficiently powered prospective clinical and intervention studies are required to determine the antioxidant effectiveness of simvastatin [84].…”
Section: Dimethyl Formamide (Dmf) Simvastatin Ginkgo Bilobamentioning
confidence: 99%
“…In a related study, we observed that the anti-oxidative stress function of Sim in dopaminergic neurons is very prominent. Previous evidence suggests that Sim is able to activate Nrf2 and respond positively to oxidative stress caused by H 2 O 2 [10]. We have determined the anti-oxidant properties of Sim.…”
Section: Introductionmentioning
confidence: 97%